PASAR DIGITAL SEBAGAI SARANA PEMASARAN HASIL TANI DESA O’BESI TIMOR TENGAH SELATAN - Claudia Olga A. Seran; Semlinda Juszandri Bulan (Universitas Boyolali, 2019)
Marketing is one of the most important things for business people. Without good marketing, it will be difficult to make the bussiness more advanced. This is also experienced by goups of farmers in the village Of O’besi subdistrict of North Mollo. The problem occurred was the result off farmers from farmer groups of O’besi village yet been absorbed entirely by the customer outside of O’besi village and subdistrict of North Mollo, lack of promotion and marketing is a major cause, besides the market organizers that are unorganized and traditional marketst that tend to slum conditions, stock piling of goods that have not efficiently caused the wheels of the economy of the farmers groups did not move well. The purpose of this responsive web-based e-commerce website is to be able to easily increase farm production output and efficient and economical stockpiling of goods for the smooth running of business activities so as to facilitate consumers and prospective consumers to obtain information and services to order products whenever and wherever even. The research results show that the e-commerce website can help the goups of farmers in the village Of O’besi in selling their product widely and the customer can buy their products easily.